Silencio - Scorsese, Martin, 1942-; Driver, Adam; Neeson, Liam, 1952-; Garfield, Andrew; Speak Up (Barcelona RBA revistas, 2016)
In the 17th century, two Portuguese Jesuit priests travel to Japan in an attempt to locate their mentor, who is rumored to have committed apostasy, and to propagate Catholicism.
EEUU, 2016
Acompaña a la revista Speak Up no. 387
Andrew Garfield, Adam Driver, Liam Neeson
No recomendada a menores de 16 años
Idiomas : Castellano, inglés
Keywords: Jesuitas; Películas cinematográficas -- DVD